2021
DOI: 10.2106/jbjs.rvw.21.00016
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Role of Technology in Rehabilitation After Lower-Extremity Joint Replacement

Abstract: Background:The effectiveness of telehealth programs in the administration of rehabilitation and the monitoring of postoperative progress after joint replacement is not well studied. The purpose of the present study was to systematically review the currently available evidence on the use of smart-device technology and telehealth programs to guide and monitor postoperative rehabilitation following total joint arthroplasty and to assess their impact on outcomes following surgery.Methods:A literature search of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…Telerehabilitation in physical therapy has been shown to be effective for both nonorthopaedic conditions and orthopaedic conditions, such as osteoarthritis, low back pain, and total joint replacement. 19,20,23 High rates of patient satisfaction were seen with the use of SSS with VCS in the current study, with 98% of patients responding positively to the impact of telehealth on the experience with SSS. Given a less than 100% rate in patient satisfaction, it stands to reason that SSS is not the optimal early postoperative rehabilitation modality for every patient.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Telerehabilitation in physical therapy has been shown to be effective for both nonorthopaedic conditions and orthopaedic conditions, such as osteoarthritis, low back pain, and total joint replacement. 19,20,23 High rates of patient satisfaction were seen with the use of SSS with VCS in the current study, with 98% of patients responding positively to the impact of telehealth on the experience with SSS. Given a less than 100% rate in patient satisfaction, it stands to reason that SSS is not the optimal early postoperative rehabilitation modality for every patient.…”
Section: Discussionmentioning
confidence: 54%
“…3 Moreover, patient satisfaction rates and functional outcomes have been shown to be similar with telerehabilitation when compared with traditional inperson rehabilitation. 8,19,20 Benefits of telemedicine in physical therapy rehabilitation include decreased patient travel, lower coronavirus exposure risk, less wait time burden, and greater patient convenience, 14 all of which may lead to higher adherence rates. The majority of patients continued to use SSS during rehabilitation at 6 weeks postoperatively, indicating that the SSS device and protocols were tolerated by patients during the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…This search was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement 6. The authors used the same methodology employed in previous studies of technology utilization in joint replacement7 and outcomes by gender in joint replacement 8. All possible combinations of the following keywords were used for the search: “healthcare disparities,” “hip arthroplasty,” “knee arthroplasty,” “hip replacement,” “knee replacement,” “total joint arthroplasty,” “joint replacement,” “THA,” “TKA,” “outcomes,” “social determinants,” “gender,” “inequities,” “inequality,” “bias,” “utilization rate,” “demographic factors,” and “sex.” The literature search was limited to studies published in the last 20 yr from February 14, 2001, to February 14, 2021.…”
Section: Methodsmentioning
confidence: 99%
“…(6) Were potential confounding variables and risk factors identified and examined using acceptable statistical techniques? (7) Was the duration of follow-up reasonable for investigated outcomes? (8) Was the population included in the study described adequately?…”
Section: Quality Appraisal and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Over the years, parallel to the institutions, many organizations from different countries have tested various types of telemedicine services, producing a base of scientific literature on the efficiency and effectiveness of the implementation of e-health services, such as telerehabilitation [ 9 ]. In the field of orthopedic rehabilitation, various systematic reviews [ 10 ] and meta-analyses [ 11 , 12 , 13 , 14 ] have shown similar clinical outcomes after face-to-face rehabilitation as compared to telerehabilitation. In Italy and worldwide, the number of joint replacement surgeries is increasing sharply; of these, hip arthroplasty is the most widely practiced, and it has been shown to be effective in ameliorating the health-related quality of life of subjects diagnosed with end-stage osteoarthritis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%